DRB1 and DRB2 Are Required for an Appropriate miRNA-Mediated Molecular Response to Salt Stress in Arabidopsis thaliana - Joseph L. Pegler; Jackson M. J. Oultram; Christopher P. L. Grof; Andrew L. Eamens (Plants)
In plants, microRNAs (miRNAs) and their target genes have been demonstrated to form an essential component of the molecular response to salt stress. In Arabidopsis thaliana (Arabidopsis), DOUBLE-STRANDED RNA BINDING1 (DRB1) and DRB2 are required to produce specific miRNA populations throughout normal development and in response to abiotic stress. The phenotypic and physiological assessment of 15-day-old wild-type Arabidopsis seedlings, and of the drb1 and drb2 mutants following a 7-day period of salt stress, revealed the drb2 mutant to be more sensitive to salt stress than the drb1 mutant. However, the assessment of miRNA abundance and miRNA target gene expression showed that the ability of both drb mutants to mount an appropriate miRNA-mediated molecular response to salt stress is defective. Furthermore, molecular profiling also showed that DRB1 and DRB2 are both required for miRNA production during salt stress, and that both a target transcript cleavage mode and a translational repression mode of RNA silencing are required to appropriately regulate miRNA target gene expression as part of the molecular response of Arabidopsis to salt stress. Taken together, the phenotypic, physiological, and molecular analyses performed here clearly show that all components of the miRNA pathway must be fully functional for Arabidopsis to mount an appropriate miRNA-mediated molecular response to salt stress.